2018
DOI: 10.1136/bcr-2018-227113
|View full text |Cite
|
Sign up to set email alerts
|

Repair of the ulnar collateral ligament of the elbow with internal brace augmentation: a 5-year follow-up

Abstract: The ulnar collateral ligament (UCL) is the primary restraint to valgus angulation at the elbow. Injury to the UCL is increasingly common and can lead to instability, especially in athletes involved in overhead throwing. Conventional treatment is reconstruction using tendon autograft but performance levels are often restricted after long periods of rehabilitation. Modern surgical techniques have led to renewed interest in repair of the ligament, with the aim of restoring native anatomy. This has the benefit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…An additional case study cited the RTP of a college football player 4 months postoperation. 35 We found high RTP rates (92.5%) at a mean 6.9 months, which is similar to results recently published by Dugas et al 10,34 Comparatively, in a large study on reconstructions, Cain et al 6 stated that 83% of patients returned to play at a mean 11.6 months.…”
Section: Discussionsupporting
confidence: 91%
“…An additional case study cited the RTP of a college football player 4 months postoperation. 35 We found high RTP rates (92.5%) at a mean 6.9 months, which is similar to results recently published by Dugas et al 10,34 Comparatively, in a large study on reconstructions, Cain et al 6 stated that 83% of patients returned to play at a mean 11.6 months.…”
Section: Discussionsupporting
confidence: 91%
“…As this is a relatively new procedure, current outcomes in the literature are limited but have demonstrated the ability to undergo early rehabilitation, accelerated return to play compared with UCL reconstruction, and favorable rates of return to play. 12 , 33 In our experience, revision procedures have not posed a major challenge. This may be because we use a polyetheretherketone polymer anchor to minimize cyst formation, tunnel expansion, or osteolysis, while permitting anchor removal in a revision setting.…”
Section: Discussionmentioning
confidence: 86%
“…Jones et al 152 reported similar results when comparing specimen repaired with internal brace with specimen reconstructed with the modified Jobe technique. Recently, Wilson et al 153 reported one case of a collegiate football athlete who suffered a complete tear of the UCL and was treated with primary UCL repair with internal brace and achieved excellent recovery with RTS at 3 months. This case also demonstrated excellent elbow function and RTP at the same level 5 years later.…”
Section: Medial Elbow Pathologymentioning
confidence: 99%
“…This case also demonstrated excellent elbow function and RTP at the same level 5 years later. 153 While the evidence regarding clinical outcomes is sparse, repair techniques with internal brace are promising and continue to gain popularity. 154 Study outcomes of reconstruction and repair techniques for UCL rupture are summarized in Tables 7 – 9 .…”
Section: Medial Elbow Pathologymentioning
confidence: 99%